2008
DOI: 10.1352/0895-8017(2008)113[307:scadpw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison and Depression: People With Mild and Moderate Intellectual Disabilities

Abstract: There has been limited research on the role of sociocognitive factors in depression with people who have a mild intellectual disability. However, an association has been found between negative social comparison and depressed mood. We extend previous work by including individuals with clinical depression. A between-groups design of 18 depressed versus 18 nondepressed participants was used. Depression measures were administered, along with measures of self-esteem and social comparison. Participants reported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Third, the different presenting problems in the sample may influence responding on many of the TEAM items. For example, negative self‐evaluative and social comparative beliefs in depression (MacMahon & Jahoda 2008; Dagnan & Sandhu 1999) may influence expectations of making an effective contribution to successful therapeutic relationships. Finally, whilst one open‐ended question addressed client motivation, it is acknowledged that it would be helpful to develop a proper motivation component of the TEAM.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the different presenting problems in the sample may influence responding on many of the TEAM items. For example, negative self‐evaluative and social comparative beliefs in depression (MacMahon & Jahoda 2008; Dagnan & Sandhu 1999) may influence expectations of making an effective contribution to successful therapeutic relationships. Finally, whilst one open‐ended question addressed client motivation, it is acknowledged that it would be helpful to develop a proper motivation component of the TEAM.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies fail to report the target group that individuals make comparisons to (e.g., whether this is fellow individuals with intellectual disabilities, or members of the community in general). At least two studies demonstrated that this makes a potentially significant difference on the types social comparisons made (MacMahon & Jahoda, ; Paterson et al., ), and the subsequent impact this can have on self‐esteem and psychological/emotional distress. Secondly, it is also important to distinguish which domains of self individuals are making social comparisons on (e.g., social attractiveness and autonomy), as these will like equally impact on subsequent psychological distress and self‐worth.…”
Section: Resultsmentioning
confidence: 99%
“…Although mixed findings were reported, a large majority of studies included in this review reported that negative social comparisons were related to higher levels of psychological distress and lower self‐esteem (Dagnan & Sandhu, ; Dagnan & Waring, ; MacMahon & Jahoda, ; McGillivray & McCabe, ; Paterson et al., ; Szivos‐Bach, ). There was some suggestion that negative social comparisons are particularly elevated in adults with intellectual disabilities who are depressed as compared to those intellectual disabilities individuals who are not depressed (MacMahon & Jahoda, ; McGillivray & McCabe, ). Results would suggest that it is in the domains of social attractiveness and capability/ability where social comparisons are particularly salient for adults with intellectual disabilities, in that individuals with intellectual disabilities are more likely to experience shame in relation to these domains of self and social roles.…”
Section: Discussionmentioning
confidence: 96%
“…The use of pictorial supports is often recommended (e.g., Hartley & MacLean, 2006) or used (e.g., MacMahon & Jahoda, 2008) when data are to be collected from individuals with an intellectual disability. Unless there is some examination of the individuals' understanding of the meanings of these supports, they may decrease reliable responding rather than ensure better quality data.…”
Section: Future Researchmentioning
confidence: 99%